2021
DOI: 10.1093/tbm/ibab100
|View full text |Cite|
|
Sign up to set email alerts
|

Engagement with a digital therapeutic for smoking cessation designed for persons with psychiatric illness fully mediates smoking outcomes in a pilot randomized controlled trial

Abstract: Understanding the mechanisms of change of digital therapeutics is a critical step to improve digital health outcomes and optimize their development. Access to and engagement with digital content is arguably a core mechanism of change of these interventions. However, the mediational role of app engagement has been largely unexamined. To evaluate the mediational effect of engaging with a digital therapeutic for smoking cessation designed for adults with psychiatric disorders. Secondary analysis of a pilot clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In summary, LTQ's design appears to effectively predict engagement with a digital therapeutic among individuals with SMI after rigorously controlling for cognitive factors. As shown elsewhere ( Browne et al, 2021 ), this finding is important since engagement with this digital therapeutic mediated clinical outcomes. Further, this tailored digital therapeutic seemed to comparably engage a broad range of individuals with different demographics and clinical characteristics from the target population.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In summary, LTQ's design appears to effectively predict engagement with a digital therapeutic among individuals with SMI after rigorously controlling for cognitive factors. As shown elsewhere ( Browne et al, 2021 ), this finding is important since engagement with this digital therapeutic mediated clinical outcomes. Further, this tailored digital therapeutic seemed to comparably engage a broad range of individuals with different demographics and clinical characteristics from the target population.…”
Section: Discussionsupporting
confidence: 69%
“…To this end, apps are increasingly utilized in the treatment of SMI in a variety of ways (e.g., stand-alone interventions, symptom monitoring, adjunctive therapeutic support) with demonstrated feasibility and efficacy ( Batra et al, 2017 ; Ben-Zeev et al, 2018 ; Bucci et al, 2018 ; Depp et al, 2016 ; Eisner et al, 2019 ; Firth and Torous, 2015 ; Fortuna et al, 2018 ; Liu et al, 2019 ). Yet, there is variable engagement with apps among users with SMI (e.g., a small subset of users often account for a large proportion of app engagement) and the real-world uptake of smartphone apps by clinics and users remains relatively low ( Torous et al, 2017 ; Torous et al, 2018 ), which is concerning given that app engagement is linked with improved outcomes ( Ben-Zeev et al, 2018 ; Best et al, 2019 ; Browne et al, 2021 ; Harvey et al, 2020 ). Therefore, knowledge of the putative barriers to app engagement in this population is necessary to guide strategies for facilitating adequate uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high population-level reach, very little is known about the potential mediators underlying the efficacy of smartphone apps for smoking cessation [ 6 ]. In the broader literature on digital interventions (eg, websites and SMS text messaging) for smoking cessation, we are aware of only 3 randomized controlled trials (RCTs) that reported on their mechanisms of action—with each showing support for the theoretical models guiding their interventions (eg, self-efficacy) [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with studies on psychological mechanisms of action, digital intervention researchers have been studying the role of intervention engagement as a process that predicts treatment outcomes [ 6 , 7 , 24 , 25 ]. Our previous study has shown that, in the SmartQuit app that preceded the iCanQuit app, engagement with the intervention and its specific ACT components was predictive of smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Our study identified 15 potential papers; of those, five interventions were delivered online [ 20 , 21 , 22 , 23 , 24 ], one detailed the development of an app [ 25 ], and one study only recruited people with mood disorders [ 26 ], so they were excluded from this review. The remaining eight studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] were included and focused on a variety of apps (Quitpal, Kick.it, QuitGuide, Learn To Quit (LTQ), and quitSTART). The key features of these app and apps interfaces, we could detect, are presented in Table 2 and Table 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%